Hit Where It Hurts: Healthcare Access and Intimate Partner Violence - Cristina Bellés Obrero; Caoimhe T. Rice; Judit Vall Castello (Institute of Labor Economics (IZA), 2023)
This paper investigates the causal link between healthcare access and the help-seeking behavior of intimate partner violence (IPV) victims. Healthcare access can be an important entry point for screening or detecting IPV. Doctors are required by law to report any injuries to a judge if they suspect they are the result of a crime and can inform and direct victims to IPV services. We exploit the 2012 reform in Spain that removed access to the public healthcare system for undocumented immigrants. We use court reports and protection order requests from the Judicial Branch of the Spanish government to perform a difference-in-differences approach, comparing the help-seeking behavior of foreign and Spanish women before and after the reform. We find that the impact of the reform was immediate; foreign women's IPV reporting and application for protection orders decreased by 12%. This effect is entirely driven by regions with stronger enforcement of the reform. We show suggestive evidence that the reform left the underlying levels of IPV incidence unaffected. Instead, the results are driven by a reduction in injury reports by medical centers. Our findings are important given the increase in migration flows globally as well as for current debates on granting/limiting access to healthcare for marginalized groups.
Keywords: I10; I12; I14; I31; 330; healthcare access; intimate partner violence; reporting; undocumented immigrants